2022
DOI: 10.1007/s00477-022-02267-2
|View full text |Cite
|
Sign up to set email alerts
|

Flood vulnerability of a few areas in the foothills of the Western Ghats: a comparison of AHP and F-AHP models

Abstract: Flooding is one of the most destructive natural catastrophes that can strike anywhere in the world. With the recent, but frequent catastrophic flood events that occurred in the narrow stretch of land in southern India, sandwiched between the Western Ghats and the Arabian Sea, this study was initiated. The goal of this research is to identify flood-vulnerable zones in this area by making the local self governing bodies as the mapping unit. This study also assessed the predictive accuracy of analytical hierarchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…In a study conducted in Kerala by Karunakaran et al, ( 2014 ), altered sensorium, hypertension, and patients over the age of 40 (who were 9.3 times more likely to die) were revealed to be independent predictors of dengue death. This underlines the need for vulnerability modelling by integrating socio-economic and physico-environmental indicators (as in Senan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…In a study conducted in Kerala by Karunakaran et al, ( 2014 ), altered sensorium, hypertension, and patients over the age of 40 (who were 9.3 times more likely to die) were revealed to be independent predictors of dengue death. This underlines the need for vulnerability modelling by integrating socio-economic and physico-environmental indicators (as in Senan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 80%
“…This fact is confirmed by the prediction accuracy score (AUC value) of the maps created in this study. The studies by Akshaya et al, ( 2021 ), Meshram et al, ( 2019 ), Tripathi et al, ( 2021 ), and Senan et al, ( 2022 ) also found F-AHP as more effective than the AHP model. Validation of the created maps is the integral part of any modelling (susceptibility, risk, or vulnerability) due to the fact that "unless validated, the map is of no operational use".…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…However, so far, the AHP and F-AHP models have never been compared for wildfire risk modeling. The AHP and F-AHP models have been compared only for assessing the efficacy of landslide susceptibility [53,54], flood susceptibility [55,56], flood vulnerability [57], and forest fire susceptibility [52]. This is the uniqueness of this study, as no researchers have assessed the prediction capability of both the AHP and F-AHP models for the demarcation of wildfire risk zones and applied different models for the comparison of two protected areas with different vegetation in any part of the world.…”
Section: Introductionmentioning
confidence: 99%